2016
DOI: 10.1515/bog-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Creative Clusters in Visegrad Countries: Factors Conditioning Cluster Establishment and Development

Abstract: Abstract. Since the accession of the Visegrad Group of countries (V4) to the European Union, the importance of clusters has increased. With growing global competitiveness and EU 12 trends, a gradual awareness of creative industries is observed in V4 countries. Therefore, this article analyses creative clusters and factors conditioning their establishment and development. On the basis of a literature review and a questionnaire survey, a mapping of creative clusters was conducted. In addition, catalysts, main mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Gong and Hassink (2016) view creative industries as one of the newest contributors to the scale and variety of economic activities dependent on the creative class. Arguably, across many countries such activities now are a lever for growth in the knowledge economy and vital catalysts for urban economic expansion and regeneration (Cunningham, 2010;Flew, 2013;Cruz, Teixeira, 2015;Flew, Pintilii et al, 2015;Tafel-Viia et al, 2015;Bialic-Davedra et al, 2016). Throughout much of the European Union creative industries are considered as "a largely untapped resource" and a "potential economic powerhouse" (Mitkus, Maditinos, 2017: 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gong and Hassink (2016) view creative industries as one of the newest contributors to the scale and variety of economic activities dependent on the creative class. Arguably, across many countries such activities now are a lever for growth in the knowledge economy and vital catalysts for urban economic expansion and regeneration (Cunningham, 2010;Flew, 2013;Cruz, Teixeira, 2015;Flew, Pintilii et al, 2015;Tafel-Viia et al, 2015;Bialic-Davedra et al, 2016). Throughout much of the European Union creative industries are considered as "a largely untapped resource" and a "potential economic powerhouse" (Mitkus, Maditinos, 2017: 1).…”
Section: Introductionmentioning
confidence: 99%
“…During the 1990s, following the recognition by the United Kingdom government of creative industries as 'central' to the making of its post-industri-al economy, there has occurred a marked upturn in international academic and policy discourse around creative industries (White, 2010;Kong, 2014;Cruz, Teixeira, 2015;Cunningham, Potts, 2015;Jones et al, 2015;Tremblay, 2015;Bialic-Davedra et al, 2016;Lampel, Germain, 2016;Lazzeretti et al, 2017;Mitkus, Maditinos, 2017). Sternberg (2017) maintains that creative segments of economies emerged and subsequently strengthened as a popular target for policy-makers in particular after the publication of Florida's (2002; seminal works on the 'creative class' .…”
Section: Introductionmentioning
confidence: 99%
“…Jurene and Jureniene (2017) and Kozina and Bole (2018) pointed out that creative clusters are established in the largest urban centres, and Kuleva (2018) noted that creative clusters in Russia are constantly seeking the interest of local authorities. In turn, the review by Bialic-Davendra et al (2016) confirmed that creative clusters are formed in the region's largest cities. Attention was also drawn to the lack of mention of clusters in regional development strategies, to the fact that their numbers decrease over time, as well as to their reliance on the financial assistance provided under OP.…”
Section: Discussionmentioning
confidence: 88%
“…Jankowska & Götz, 2017). Among papers devoted to creative clusters in Central and Eastern Europe is that by Bialic-Davendra et al (2016) dealing with the condition and operating strategy of creative clusters. As Bontje et al (2011) and Marková (2014) have demonstrated, the specificity of Central and Eastern Europe lies in the fact that creative clusters operating here depend on financial assistance from operational programmes (OP).…”
Section: The Concept Of Industrial Clusters Including Creative Clustmentioning
confidence: 99%
“…(2013); Bialic- Davendra et al (2013Davendra et al ( , 2014Davendra et al ( , 2016; Markova (2014). The flow of knowledge within clusters was studied, among others, by Dyba (2016aDyba ( , 2016b.…”
Section: Literature Reviewmentioning
confidence: 99%